Essential readings in world politics - Mingst, Karen A. 1947-; Snyder, Jack L. (Norton series in world politics, 2008)
Introduces students to literature on international relations - from classics in the field to contemporary debates among scholars. This book offers diverse perspectives on topics such as Iran's nuclear ambitions, global health threats like avian flu, and the international reach of political Islam.